PENERAPAN KARAKTER DISIPLIN PADA SISWA KELAS 1 DI MASA PANDEMI COVID-19 - Nastiti, Dian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study aims to analyze the application of the discipline character of elementary school students in the brave learning period. The impact of the COVID-19 pandemic on character education which must also be carried out boldly, one of which is the value of disciplined character. This study uses a descriptive qualitative research with the research subjects of grade 1 students at Masdrasah Ibtidaiyah At Tijani. Methods of data collection using observation, interviews, and documentation. The data collected is then analyzed by means of data reduction, data presentation, and drawing conclusions. The results of this study indicate that during distant learning all students apply the character of discipline in every school activity. Teachers and schools apply disciplined character to students by 1) daily activities, namely: presence on time, discipline of worship by presenting evidence that children have worshiped at home before learning and other worship activities that are arranged, disciplined learning with students' punctuality do the task and the learning process. 2) Programmed activities, which are carried out with activities programmed by teachers and schools, such as memorizing the Qur'an and praying, self-hygiene discipline and the school environment.